Macrobenthos as an indicator of water quality assessment in Kutaraja Fishing Port, Indonesia - Makwiyah A Chaliluddin; Shella Yusnita; Thaib Rizwan; Sayyid Afdhal El Rahimi; Ichsan Rusydi; Roesa Nellyana (Depik, 2022)
Water quality is influenced by the high activity in the port area, resulting in decreasing water quality. The biological parameters based on the structure of the aquatic community of organisms that act as bioindicators could be indicated as changes in water quality around the port. Bioindicators are a group of living organisms susceptible to environmental changes due to human activities and natural damage. One of the aquatic organisms that can be used as an indicator of water quality is Benthos because of its sedentary nature. This study aims to determine the quality of the water environment seen from the benthic community structure, namely density, diversity index, uniformity and dominance index, to embody the clean and pollution-free Kutaraja Fishing Port. The research shows that the aquatic environment of Kutaraja Fishing Port is included as the less stable category with a moderate diversity value (H' 1) but has high benthic individual uniformity (E 0.6), which means that individuals are evenly distributed a low dominance value or C is close to 0.Keywords:Water qualityBio-indicatorBenthosKutarajaBanda Aceh